Analisis Kemampuan Belajar Mahasiswa Ditinjau dari Self Regulated Learning - Maesaroh Lubis; Rikha Surtika Dewi; Dendi Yuda S.; Nurlaila Wahidah (NANAEKE: Indonesian Journal on Early Childhood Education, 2022)
The implementation of online learning as a result of the pandemic situation requires today's students to have self-regulated learning. Self Regulated Learning (SRL) is very dependent on individual factors because it requires the ability to adjust from the habit of attending face-to-face learning to distance learning. An individual is considered to have self-regulated learning skills if there are a number of indicators marked by the ability to set goals, choose strategies, and monitor and motivate themselves so that they can continue to attend learning optimally. In this regard, this study aims to determine the level of self-regulated learning in FKIP UMTAS students and the IAIC Tarbiyah Faculty which involved 173 participants who came from 57 UMTAS PGSD first-year students, 44 UMTAS PGPAUD students, and 72 IAIC PBA students. The determination of the participants used a purposive sampling technique and the type of analysis used a quantitative percentage analysis. Data were collected using a Likert scale questionnaire which contained several statements about self-regulated learning. The results showed that the average self-regulated learning of students in the two universities was in the medium category with a percentage of 67%. The results of the study showed good control of students in participating in distance learning activities which contributed to the smooth running of learning activities.